2007
DOI: 10.1111/j.1745-4522.2007.00092.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Stearidonic Acid on Lipoprotein Secretion and Fatty Acid Composition in Hepg2 Cells

Abstract: The health benefits of w-3 fatty acids, particularly fish oils, are well known. It is generally recommended to obtain w-3 fatty acids from fatty fish; however, the possible contaminants in fish products may deter this. Thus, supplements of w-3 fatty acids from plant-originated lipids may be of interest. Among these, a-linolenic acid (ALA) and stearidonic acid (SDA) have drawn attention. Thus, the purpose of this research was to test the possible conversion of these fatty acids, particularly SDA, to eicosapenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Although cis-9, trans-11 is the main CLA isomer in natural food, 17 the isomer trans-10, cis-12 is reported to affect energy metabolism and body-fat deposition and composition in mice. 13 Other studies in murine 3T3-L1 adipocytes have shown smaller lipid droplets in differentiated cells treated with trans-10, cis-12 CLA 14 as well as a higher influence on lipid metabolism, energy expenditure and fatty acid oxidation in 3T3-L1 adipocytes. 15,7 In humans results are controversial and studies have not shown either cis-9, trans-11 or trans-10, cis-12 CLA isomer to significantly affect body weight.…”
Section: ■ Materials and Methodsmentioning
confidence: 93%
See 1 more Smart Citation
“…Although cis-9, trans-11 is the main CLA isomer in natural food, 17 the isomer trans-10, cis-12 is reported to affect energy metabolism and body-fat deposition and composition in mice. 13 Other studies in murine 3T3-L1 adipocytes have shown smaller lipid droplets in differentiated cells treated with trans-10, cis-12 CLA 14 as well as a higher influence on lipid metabolism, energy expenditure and fatty acid oxidation in 3T3-L1 adipocytes. 15,7 In humans results are controversial and studies have not shown either cis-9, trans-11 or trans-10, cis-12 CLA isomer to significantly affect body weight.…”
Section: ■ Materials and Methodsmentioning
confidence: 93%
“…This is consistent with previous studies indicating the trans-10, cis-12 isomer as the active isomer with regard to antiobesity in different experimental models such as cell cultures 7 and animals. 13,16,43 Unfortunately, the antiobesity effects of trans-10, cis-12 CLA isomer in humans remain unclear due to the presence of other intrinsic experimental parameters such as the dose used, study length or exercise. 10,44 Herein, the effectiveness of Tonalin added to a food matrix has been demonstrated.…”
Section: ■ Discussionmentioning
confidence: 99%
“…In experiment 2, CLA fed animals had body weights similar to restricted animals and CLA significantly reduced body fat (significantly lower than prior to and post restriction, or pair fed). This suggests that CLA exerted modulation of body fat independent of reduced food intake, CLA may be more effective at protecting against fat mass regain following weight loss than as a loss treatment (Park et al, 2007). Bifidobacterium, Bifidobacterium pseudolongum, and Bifidobacterium breve can convert free linoleic acid and a-linolenic acid to different CLA (Yeganeh et al, 2017).…”
Section: Other Mechanismsmentioning
confidence: 99%